The Evidence for Hospitals in Early India - Wujastyk, Dominik (History of Science in South Asia)

(untitled) (University of Alberta Library, 2022)
The article surveys the history of South Asian literature and epigraphy for reliable evidence regarding the existence of early hospitals. It explores the reasons that may account for the exclusion of South Asian data from international scholarship on the history of hospitals. The widely-repeated idea that King Aśoka built hospitals is refuted. Nevertheless, hospitals may be very early in India. It is suggested that scholarly medical literature on the building and equipping of a hospital was transmitted to Baghdad in the late eighth century and influenced the construction of early Islamic hospitals.